A newly characterized allele of ZmR1 increases anthocyanin content in whole maize plant and the regulation mechanism of different ZmR1 alleles - Luo, Meijie; Lu, Baishan; Shi, Yaxing; Zhao, Yanxin; Wei, Zhiyuan; Zhang, Chunyuan; Wang, Yuandong; Liu, Hui; Shi, Yamin; Yang, Jinxiao; Song, Wei; Lu, Xiaoduo; et al. (Theoretical and applied genetics, 2022)
Key message The novel ZmR1 CQ01 allele for maize anthocyanin synthesis was identified, and the biological function and regulatory molecular mechanisms of three ZmR1 alleles were unveiled. Anthocyanins in maize are valuable to human health. The R1 gene family is one of the important regulatory genes for the tissue-specific distribution of anthocyanins. R1 gene allelic variations are abundant and its biological function and regulatory molecular mechanisms are not fully understood. By exploiting genetic mapping and transgenic verification, we found that anthocyanin pigmentation in maize leaf midrib was controlled by ZmR1 on chromosome 10. Allelism test of maize zmr1 EMS mutants confirmed that anthocyanin pigmentation in leaf sheath was also controlled by ZmR1 . ZmR1 CQ01 was a novel ZmR1 allelic variation obtained from purple maize. Its overexpression caused the whole maize plant to turn purple. ZmR1 B73 allele confers anthocyanin accumulation in near ground leaf sheath rather than in leaf midribs. The mRNA expression level of ZmR1 B73 was low in leaf midribs, resulting in no anthocyanin accumulation. ZmR1 B73 overexpression promoted anthocyanin accumulation in leaf midribs. Loss of exon 5 resulted in ZmR1 ZN3 allele function destruction and no anthocyanin accumulation in leaf midrib and leaf sheath. DNA affinity purification sequencing revealed 1010 genes targeted by ZmR1 CQ01 , including the bz2 in anthocyanin synthesis pathway. RNA-seq analysis showed 55 genes targeted by ZmR1 CQ01 changed the expression level significantly, and the expression of genes encoding key enzymes in flavonoid and phenylpropanoid biosynthesis pathways were significantly up-regulated. ZmR1 functional molecular marker was developed. These results revealed the effects of transcriptional regulation and sequence variation on ZmR1 function and identified the genes targeted by ZmR1 CQ01 at the genome-wide level.